2021
DOI: 10.1002/mma.7228
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of kernel functions‐based approach with Atangana–Baleanu–Caputo distributed order derivative for solutions of fuzzy fractional Volterra and Fredholm integrodifferential equations

Abstract: Mathematical modeling of uncertain fractional integrodifferentials (FIDEs) is an extremely significant topic in electric circuits, signal processing, electromagnetics, and anomalous diffusion systems. Based on the reproducing kernel algorithm (RKA), a touching numerical approach is considering in this study to solve groups of fuzzy fractional integrodifferentials (FFIDEs) with Atangana-Baleanu-Caputo (ABC) fractional distributed order derivatives. The solution-based approach lies in generating infinite orthogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…From literature, it is believed that modeling of physical and real problems using non-integer order derivative is more precise compared to integer-order derivatives [30], [58]. The main advantages of using fractional order derivative in disease dynamics is that, they can properly capture the memory effects and hereditary properties of species that exist in biological systems [31], [32], [54], [15], [58]. Additional, it is believed that cell membrane of living organisms containing some fractional-order electrical conductance which are classified in the groups of non-integer order models.…”
Section: Introductionmentioning
confidence: 99%
“…From literature, it is believed that modeling of physical and real problems using non-integer order derivative is more precise compared to integer-order derivatives [30], [58]. The main advantages of using fractional order derivative in disease dynamics is that, they can properly capture the memory effects and hereditary properties of species that exist in biological systems [31], [32], [54], [15], [58]. Additional, it is believed that cell membrane of living organisms containing some fractional-order electrical conductance which are classified in the groups of non-integer order models.…”
Section: Introductionmentioning
confidence: 99%
“…[11,16,19,23,25,38] and [25] discussed various statistical tests for circular observations under fuzzy logic. More information on the applications of the fuzzy-based analysis can be seen in [1,4] and [5]. [34] introduced the neutrosophic (a study between true and false) logic that is found to be more efficient than fuzzy logic.…”
Section: Introductionmentioning
confidence: 99%
“…In the answer to the renowned mathematician L' Hospital's question, if d m dv m , then what does it mean if m = 1/2, different explanations of the fractional derivative are presented. The most famous approaches to fractional derivatives are Caputo derivative, Letnikove, and R-L derivative [12,13]. Few properties of these fractional-order derivatives are similar to the classical order derivatives.…”
Section: Introductionmentioning
confidence: 99%